(3YOI CQGLjR abgjIs - (3GdYGedj, GdMQ, eMeO Hf GdMSf Hf Ydj, J(B1104(3g`s
(3ChdgG (B:s
(3bGd eMeO Hf GdMSf GdMQ GdYGedj aj efRhMGJ GdHFQ(B: (3jfRM eGA GdHQ ddHYjQ(B***(3heGFY GdeScQ hGdNehQs
(3BNQgG (B:s
(3BNQg ef efXheI GdehGQjK HGH ejQGK GdeLhS(B: (3OGFeI eG OGQJ GdCadGc(B***(3hSHMJ NGdbgG GdCadGcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B90s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis